Digital marketing of smokeless tobacco: A longitudinal analysis of exposure and initiation among young adults. (June 2021) - Clendennen, Stephanie L.; Mantey, Dale S.; Wilkinson, Anna V.; Perry, Cheryl L.; Harrell, Melissa B.; Loukas, Alexandra
Highlights: 14.6% of young adults reported exposure to digital smokeless tobacco marketing. Racial/ethnic minorities were significantly more likely than their white peers to report exposure. Exposure was significantly associated with smokeless tobacco uptake one-year later. Abstract: Objectives: This study examines the relationships between recall of exposure to digital marketing of smokeless tobacco, via the internet and social media, and subsequent initiation of smokeless tobacco use at one-year follow-up, among young adult never users of smokeless tobacco in Texas. Methods: Data were from waves 6 (Spring 2017) and 7 (Spring 2018) of the Marketing and Promotions Across Colleges in Texas Study (Project M-PACT); a longitudinal study of two- and four-year Texas college students. Participants were 2731 young adult never smokeless tobacco users (ages 20–32) with complete data at both assessment periods. A multi-level, multiple logistic regression model was applied, accounting for school clustering, to examine the relationship between recall of exposure to digital marketing of smokeless tobacco at baseline (wave 6) and smokeless tobacco use initiation at one-year follow-up (wave 7). Analyses controlled for important baseline covariates (socio-demographic factors, other marketing exposure, other tobacco product use). Results: Overall, 14.6% of never smokeless tobacco users reported exposure to smokeless tobacco marketing via digital media. Exposure to digital marketing of smokeless tobacco at baseline was associated with greater odds of smokeless tobacco use initiation among young adult never users (AOR: 2.14; 95%CI: 1.12 – 4.06) at one-year follow-up. Conclusions: Findings reveal exposure to smokeless tobacco marketing via digital media was common. Further, there appears to be a strong relationship between this exposure and subsequent smokeless tobacco use among young adult never smokeless tobacco users.